Hold on to your friends: Dedicated chaperones of ribosomal proteins: Dedicated chaperones mediate the safe transfer of ribosomal proteins to their site of pre‐ribosome incorporation. (17th November 2016) - Pillet, Benjamin; Mitterer, Valentin; Kressler, Dieter; Pertschy, Brigitte
Abstract : Eukaryotic ribosomes are assembled from their components, the ribosomal RNAs and ribosomal proteins, in a tremendously complex, multi‐step process, which primarily takes place in the nuclear compartment. Therefore, most ribosomal proteins have to travel from the cytoplasm to their incorporation site on pre‐ribosomes within the nucleus. However, due to their particular characteristics, such as a highly basic amino acid composition and the presence of unstructured extensions, ribosomal proteins are especially prone to aggregation and degradation in their unassembled state, hence specific mechanisms must operate to ensure their safe delivery. Recent studies have uncovered a group of proteins, termed dedicated chaperones, specialized in accompanying and guarding individual ribosomal proteins. In this essay, we review how these dedicated chaperones utilize different folds to interact with their ribosomal protein clients and how they ensure their soluble expression and interconnect their intracellular transport with their efficient assembly into pre‐ribosomes. Abstract : Unassembled ribosomal proteins are prone to aggregation, hence requiring mechanisms for their safe delivery. In this essay, we review how dedicated chaperones capture individual ribosomal protein clients and how they ensure their soluble expression and interconnect their intracellular transport with their efficient assembly into pre‐ribosomes.